Pengaruh Gaya Hidup dan Literasi Keuangan Terhadap Manajemen Keuangan Pribadi pada Gen Z Muslim di Surabaya - Muhammad Fakhri Dzulfikar; Bibi Faiza Farhana; Akhlis Fathikul Islam; Musaidatul Maulidiyah; Fata Habibullah; Maryam Bte Badrul Munir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to investigate whether lifestyle and financial literacy affect personal financial management in generation Z in Surabaya City. This study uses an associative quantitative research method with all students of Surabaya State University, while the sample used is Muslim students at the Faculty of Economics and Business, Surabaya State University. Data analysis used is the same validity test rehabilitation, normality test, multiple regression test, hypothesis test (t & f) then obtains results for financial literacy and lifestyle variables, the significance value in the F Test is less than 0.005 and the value of f-count> f-table which means Financial Literacy and Lifestyle have a significant effect simultaneously on the Personal Financial Management variable. The Financial Literacy variable has a positive and significant partial effect on Personal Financial Management with the results of the significance value in the T Test which is less than 5% (0.05) and the value of t-count is greater than t-table. While the Lifestyle variable has a negative and insignificant partial effect on Personal Financial Management with the results of the significance value in the T Test which is greater than 5% (0.05) and the value of t-count is smaller than t-table.